Leadership Quality in the Millennial Era in Achieving Organizational Goals - Abdul Aziz; Ratni Prima Lita; Rida Rahim; Veri nita (Politeknik Negeri Bengkalis, 2023)
Becoming a leader in the era of the industrial revolution and the evolution of society or better known as the millennial era requires a different leadership style. George Bradt said,